2022
DOI: 10.14295/cs.v13.3820
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical characteristics of alternative substrates and fertilization on the growth and quality of Spondias macrocarpa seedlings

Abstract: The objectives were to determine the physical and chemical characteristics of different substrates, and assess the influence of different substrates, with and without the addition of controlled-release fertilizer, on the growth and morphological quality of taperebá (Spondias macrocarpa) seedlings. The experimental design adopted was a 2 x 6 factorial scheme, with the presence and absence of 8.0 g L-1 of encapsulated controlled-release fertilizer and six substrates [Sub1= soil; Sub2= soil + carbonized rice husk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…2 Furthermore, the requirement for phosphorus varies depending on the plant and the growing methods, like aquaponics needing less phosphorus compared to hydroponics. 1,2,4–7 For instance, one study reported that the average concentrations of phosphate (PO 4 –P) used in the aquaponic and hydroponic systems were 20 mg l −1 (0.62 mM) and 149 mg l −1 (4.62 mM), respectively. 3 Therefore, the phosphorus content should be closely monitored in aquaponic and hydroponic systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, the requirement for phosphorus varies depending on the plant and the growing methods, like aquaponics needing less phosphorus compared to hydroponics. 1,2,4–7 For instance, one study reported that the average concentrations of phosphate (PO 4 –P) used in the aquaponic and hydroponic systems were 20 mg l −1 (0.62 mM) and 149 mg l −1 (4.62 mM), respectively. 3 Therefore, the phosphorus content should be closely monitored in aquaponic and hydroponic systems.…”
Section: Introductionmentioning
confidence: 99%